SEASONAL VARIATION IN STROKE IN A TEACHING HOSPITAL OF KHYBER PAKHTUNKHWA - ., Ziauddin; Iqbal, Naveed; shah, ishfaq ahmad; Ali, Zafar; Rehman, Haleem ur; Mehmood, Khalid (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine seasonal variation in the occurrence of stroke and its subtypes (ischemic stroke and hemorrhagic stroke) during summer and winter and to observe the frequency of common risk factors for stroke. Methodology: The present descriptive study was conducted in the Depart -ment of Medicine, MTI Lady Reading Hospital Peshawar, Khyber Pakhtunkhwa, Pakistan, over a period of one year from 1st January 2014 to 31st December 2014. A total of 321 patients of any age and either gender were included. The diagnosis was established based on history, clinical examination and supple-mented by CT scan of brain. Results: In winter 58.56% of patients and in summer 41.48% of patients were presented. Ischemic stroke was present in 66.04% patients while hemorrhagic stroke in 33.95% patients. Males had more strokes as compared to females (60.75% Vs. 39.25%). In males highest number of strokes was found in 60-69 age groups whereas in females it was in 50-59 age groups. In winter the strokes increased in all age groups comparative to summer. Hypertension (34.26%) was the highest risk factor for stroke. Conclusion: Stroke showed seasonal variation. Winter season was associated with increased frequency of stroke and its subtype of hemorrhagic stroke. There was variation of gender, season and stroke types in different age groups. Hypertension was found to be the highest risk factor.